National Survey of Neonatal–Perinatal Medicine Fellows on Postresuscitation Debriefing - Guo, Lily; Sather, Nicole K.; Khan, Nadia; Zinns, Lauren E.; Havalad, Vinod; Brennan, Gillian (American Journal of Perinatology, 2025)
Debriefing can be a powerful tool to facilitate improvement of performance after a resuscitation event. This study characterizes the debriefing experience of neonatal–perinatal medicine (NPM) fellows in the neonatal intensive care unit (NICU), operating room, and delivery room in the United States.An anonymous 13-item electronic survey was distributed to NPM program directors across the United States, who were asked to forward it to their respective NPM fellows. The survey addressed the frequency and timing of debriefings, access to formal training, and comfort levels with debriefing.Ninety-five responses were collected, with all participants having taken part in at least one medical resuscitation. Debriefings occurred approximately 25% of the time following a resuscitation, typically within 6 hours. Twenty percent of respondents reported feeling somewhat or very uncomfortable leading a debriefing, while 84% believed debriefings improve team performance. Despite 72% reporting no formal debriefing training, 94% expressed interest in receiving such training.This national survey on NPM fellows highlights inconsistent debriefing practices despite recognized benefits. Limited formal training remains a barrier, but a strong interest in further education presents an opportunity to improve training through the incorporation of structured debriefing frameworks into fellowship curricula.
Keywords: neonatal; debriefing; resuscitation; delivery room; NICU